2006
DOI: 10.1001/archsurg.141.8.800
|View full text |Cite
|
Sign up to set email alerts
|

Alarming Surge in Nonsurvivable Urban Trauma and the Case for Violence Prevention

Abstract: Hypothesis: A growing proportion of urban trauma mortality is characterized by devastating and likely nonsurvivable injuries.Design: Consecutive samples from prospectively collected registry data.Setting: University level I trauma center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Statistics from the US Department of Justice indicate that women accounted for 17% of firearm homicide victims between 1976 and 2004. 5 Efron et al 12 found that women represented approximately 12% of penetrating trauma patients, data which is supported by the National Vital Statistic System and the National Electronic Injury Surveillance system. 13 Arbuckle et al 8 examined female homicides in New Mexico and concluded that firearms were almost twice as likely to be used in intimate partner homicides than in nonintimate partner homicides.…”
Section: Discussionmentioning
confidence: 95%
“…Statistics from the US Department of Justice indicate that women accounted for 17% of firearm homicide victims between 1976 and 2004. 5 Efron et al 12 found that women represented approximately 12% of penetrating trauma patients, data which is supported by the National Vital Statistic System and the National Electronic Injury Surveillance system. 13 Arbuckle et al 8 examined female homicides in New Mexico and concluded that firearms were almost twice as likely to be used in intimate partner homicides than in nonintimate partner homicides.…”
Section: Discussionmentioning
confidence: 95%
“…For example, patients with penetrating trauma typically experience short EMS times because of proximity to urban hospitals, while patients injured in MVCs experience longer prehospital times because of greater distance from trauma centers and time required for safe extrication. Patients with penetrating injuries are also at higher risk for early inhospital death, 16,17 whereas deaths in patients with blunt injuries who survive EMS transport are more likely to occur later. Therefore, trauma centers with the shortest prehospital times are often those situated to receive a greater proportion of patients with critical penetrating injuries and fewer with blunt multisystem trauma, translating to a patient case mix at higher risk for death in the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that individuals living in urban areas had higher risk for late-stage presentation of breast, colorectal, lung, and prostate cancers, a pattern termed urban disadvantage (2124). There is an alarming increase in fatal urban trauma (25), which is disproportionately suffered by young, impoverished black and Latino males (4, 26). Both minority race and low insurance status are strongly associated with worse outcomes following traumatic injury (11, 27).…”
Section: Current Conditionsmentioning
confidence: 99%